Outcome following osteosynthesis or primary arthrodesis of calcaneal fractures: A cross-sectional cohort study. Issue 10 (October 2017) - Dingemans, Siem A.; Meijer, Sjoerd T.; Backes, Manouk; de Jong, Vincent M.; Luitse, Jan S.K.; Schepers, Tim
Abstract: Background: Calcaneal fractures are uncommon and have a substantial impact on hindfoot function and quality of life. Several surgical treatment options are available; both in surgical approach and type of operation. The aim of this study was to compare functional outcome and quality of life following ORIF and primary arthrodesis. Furthermore, predictors of worse functional outcome were explored. Methods: A retrospective cross-sectional cohort study was performed in patients with surgical fixation of a calcaneal fracture with a minimum follow-up of 18 months. Patients received ORIF through the 1) Extended Lateral Approach (ELA), 2) Sinus Tarsi Approach (STA) or 3) primary arthrodesis via STA. Participants were presented a questionnaire containing demographics, the AOFAS hindfoot scale, Foot Function Index, SF-36, EQ-5D and patient satisfaction. Results: In total 95 patients participated in this study. The three groups were comparable regarding patient characteristics. A median score of 74.5 points on the AOFAS hindfoot scale and 11.9 on the FFI was found for the entire group. There were no statistically significant differences between patients with ORIF of primary arthrodesis. Patients scored a median of 49.0 on the Physical Component Scale of the SF-36 and 55.4 on the Mental Component Scale. On the EQ-5D patients scored a median of 0.8 points. Again no statistically significant differences were observed between the three subgroups. Socio-economic status was the only statistically significant predictor of worse functional outcome (β: 4.06, 95% CI: 0.50–7.62) after multivariable analysis. Interpretation: Good midterm outcomes following in terms of functional outcome and in quality of life are observed. We observed no statistical significant difference in functional outcome between patients with ORIF and patients with primary arthrodesis. The only predictor of worse functional outcome is a lower socio-economic status.